Sport, Exercise, and Performance Psychology Theories and Applications. - Mugford, Angus; Cremades, J. Gualberto (Milton : Routledge, 2018)
This book brings together world-class professionals to share theoretical understanding applied to sport, exercise and performance domains. It highlights how to be more effective in developing psychological skills, context and understanding for educators, students and professionals. From both academic and practitioner perspectives, this book takes readers through contextual understanding of this field of study and into a wide variety of important areas. Specifically, the chapters focus on the mind-body relationship and performance challenges, and on core mental skills applied across different sport, exercise and performance examples (including professional athletes, normal exercise populations and military service members) The final section expands the context into the role of relationships and performance in group settings to cover a broad practice of modern day applied performance psychology.
12 Theories and Applications of Motivation in Sport, Exercise and Performance13 Goal Setting; 14 Attention and Concentration; 15 The Psychophysiology of Self-Regulation; 16 Imagery in Sport, Exercise and Performance; 17 Confidence; 18 Routines, Preparation and Performance; PART IV: The Role of Relationships and Performance in Groups; 19 Group and Team Dynamics; 20 Communication; 21 Leadership; Index
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.